Humic acid differentially improves nitrate kinetics under low‐ and high‐affinity systems and alters the expression of plasma membrane H+‐ATPases and nitrate transporters in rice. (14th November 2016) - Tavares, O.C.H.; Santos, L.A.; Ferreira, L.M.; Sperandio, M.V.L.; da Rocha, J.G.; García, A.C.; Dobbss, L.B.; Berbara, R.L.L.; de Souza, S.R.; Fernandes, M.S.
Abstract: Humic acids (HAs) have a major effect on nutrient uptake, metabolism, growth and development in plants. Here, we evaluated the effect of HA pretreatment applied with a nutrient solution on the uptake kinetics of nitrate nitrogen (N‐NO3 − ) and the metabolism of nitrogen (N) in rice under conditions of high and low NO3 − supply. In addition, the kinetic parameters of NO3 − uptake, N metabolites, and nitrate transporters (NRTs) and the plasma membrane (PM) H + ‐ATPase gene expression were examined. The plants were grown in a growth chamber with modified Hoagland and Arnon solution until 21 days after germination (DAG), and they were then transferred to a solution without N for 48 h and then to another solution without N and with and without the addition of HAs for another 48 h. After this period of N deprivation, the plants received new nutrient solutions containing 0.2 and 2.0 mM N‐NO3 − . Treatment of rice plants with HA promoted the induction of the genes OsNRT2.1‐2.2 / OsNAR2.1 and some isoforms PM H + ‐ATPase in roots. The application of HAs differentially modified the parameters of the uptake kinetics of NO3 − under both concentrations. When grown with 0.2 mM NO3 −, the plants pretreated with HA had lower K m and C min values as well as a higher V max / K m ratio. When grown with 2 mM NO3 −, the plants pretreated with HA had a higher V max value, a greater root and shoot mass, and a lower root/shoot ratio. The N fractions were also altered by pretreatment with HA, and a greater accumulation of NO3 − and N‐amino was observed in the roots and shoots, respectively, of plants pretreated with HA. The results suggest that pretreatment with HA modifies root morphology and gene expression of PM H + ‐ATPases and NO3 − transporters, resulting in a greater efficiency of NO3 − acquisition by high‐ and low‐affinity systems.